INFLUENCE ON PHOTOELECTRIC PARAMETERS OF NON-UNIFORM LIGHT ABSORPTION IN STRUCTURES BASED ON a-Si:H (American Journal of Technology and Applied Sciences, 2023)
In this manuscript gives the conclusion of an analytical expression that determines the dependence of the height of the potential barrier, which is obtained upon unevenly light absorption of over the thickness of the i-layer in the target of video with n-i-p structures based on a-Si:H, on the light intensity. In addition, it is investigated that the dependence of the width of space charge region (SCR) on certain features of a-Si:H .